Role of aminoethoxyvinylglycine in creasing of sweet orange [Citrus sinensis (L.) Osbeck] fruit - Hussain, Zahoor; Singh, Zora (Journal of Pure and Applied Agriculture, 2023)
Creasing is a physiological disorder in the rind of sweet orange [Citrus sinensis (L.) Osbeck] fruit and causes serious economic losses. The current study was conducted at Westralian fruit farm Gingin, WA-Australia during year 2011 and 2012.